Maqāṣid al-Usrah's Ambivalence in the Judge's Consideration of the Refusal of Polygamy License - Muhammad Ali Al Awshat; Umi Sumbullah; M. Aunul Hakim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study analyzes the Decision of the Lubuk Pakam Religious Court No. 0007/Pdt.G/2019/PA. LPKs who refuse applications for polygamy licenses even though the cumulative conditions have been met, use the lens of Maqāṣid al-Usrah Jamāl al-Dīn 'Aṭiyyah. The evaluation was focused on the judge's ratio decidendi to the achievement of the seven dimensions of family goals. The normative juridical research method is applied implementively through the legal syllogism method and doctrinal analysis, where the judge's legal considerations are directly confronted with the seven pillars of the sharia family. The novelty of this research lies in a holistic critique of the formalistic tendency of judges to ignore post-verdict sociological excesses. The author argumentatively asserts the existence of acute ambivalence in the verdict: on the one hand the judge succeeded in protecting the dimension of taḥqīq al-sakīnah wa al-mawaddah wa al-raḥmah of the first harmonious family, but on the other hand was passive in the threat of the collapse of the dimension of tanẓīm al-'alāqah bayn al-jinsayn, ḥifẓ al-nasl wa al-nasab, and Tanẓīm al-jānib al-mu'assasī wa al-mālī li al-usrah. The socio-legal implications of this ruling suggest that mere administrative restrictions without comprehensive mitigation actually trigger the migration of perpetrators to serial polygamous practices that strip them of legal protection and civil rights of the second wife and children who are born.